Sistem Pendukung Keputusan Pemilihan Bahan Bakar Sepeda Motor Matic Mengunakan Metode Simple Additive Weighting (SAW) - Renny Puspita Sari; Muhammad Rizqi Darmawan (STMIK Budi Darma, 2021)
Fuel oil is the main requirement when people want to drive, one of the vehicles is an automatic motorbike which is widely used by the community. There are many fuels at the gas station, namely premium, pertalite and pertamax. In choosing community fuels, there are still many things to consider, both in terms of quality, price, fuel efficiency, and others. From these various considerations, people must be confused about which one is suitable for their needs. For this reason, there is a DSS (Decision Support System) for selecting motorcycle fuel to assist in finding the appropriate fuel. This system was created using the MADM (Multiple Attribute Decision Making) method to find alternatives to various criteria, including the SAW (Simple Additive Weighting) method to find a rating for each weighted criterion. In the SAW method, the largest rating is the result of alternative choices. The calculation result of the method is if the selected alternative meets the predetermined criteria. In this study, the results of the calculation simulation obtained through the survey are pertalite fuel with the final rating of 0.718, while Pertamax is 0.716 and premium is 0.665